DETERMINING FACTORS FOR INSTRUCTORS IN THE USE OF MOOCS. - AYDIN, Gamze; BOZKURT, Serdar (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2020)
The aim of this research is to examine the relationship between instructors' use of Massive Open Online Courses (MOOCs) and their demographic characteristics. MOOC research in the literature is predominantly on students' attitudes and behaviors. However, there are fewer studies on instructors' attitudes and behaviors, which make up a significant portion of MOOC users. Therefore, the research data were collected from 181 instructors through an online questionnaire. As a result of the research, it was observed that the instructors of some faculties (Economics and Administrative Sciences, Science and Literature, Engineering Faculty) benefit more from MOOC providers. It has been determined that female instructors value the certificates earned from MOOCs more in business life. Moreover, it has been determined that instructors working at public and private sectors give importance to using MOOCs at the same level. It was also concluded that the MOOC utilization of instructors who are younger and in the first five years of their careers is higher.